A staged hybrid approach to an aberrant right subclavian artery with symptomatic Kommerell's diverticulum. Issue 3 (29th March 2021) - Dinh, Krystal; Manuel, Lucy; Perera, Kalpa; Daly, Thomas
Abstract: Aberrant right subclavian is a rare anomaly presenting in 0.3–3.0% of the population. Kommerell's diverticulum is an aneurysm associated with this phenomen; data relating to its incidence is sparse. Currently there are no well-established guidelines for the treatment of Kommerell's diverticulum, limitation being the rare occurrence of disease and heterogenous population with disease presentation. This case report illustrates a novel approach to the repair of a symptomatic Kommerrel's diverticulum with severe coronary disease. Management should be tailored on a case by case basis to the individual patient.